Prevention of the risk of money laundering. Case Colombia and Ecuador - Ortiz Luzuriaga, María Tamara; Flores Sanchez, José; Caicedo Leones, Walter; Ordoñez Guartazaca, Marjorie (Revista Universidad de Guayaquil, 2021)
The money laundering is a problem that affects the economies of the countries, since it generates a monetary issue that strengthens illicit extra-bank markets with increasingly complex operating procedures, and whose activities are international in scope. Ecuador presents high levels of risk to illicit activities such as money smuggling or money laundering because it is in a geographical area with high levels of corruption. Consequently, this article aims to summarize a referential frameworkof the main methodologies for detecting the risk of this phenomenon that affects society. For this, a methodology was followed with a qualitative approach based on the documentary review of scientific databases as well as annual reports from control bodies. It is evident that Colombian regulation considers several models aimed at different economic activities to identify, prevent and monitor risk
Keywords: Money laundering; Illicit Markets; Risk Detection